If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -36 = 12x + -24 Reorder the terms: -36 + 18x = 12x + -24 Reorder the terms: -36 + 18x = -24 + 12x Solving -36 + 18x = -24 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -36 + 18x + -12x = -24 + 12x + -12x Combine like terms: 18x + -12x = 6x -36 + 6x = -24 + 12x + -12x Combine like terms: 12x + -12x = 0 -36 + 6x = -24 + 0 -36 + 6x = -24 Add '36' to each side of the equation. -36 + 36 + 6x = -24 + 36 Combine like terms: -36 + 36 = 0 0 + 6x = -24 + 36 6x = -24 + 36 Combine like terms: -24 + 36 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 2.2=-log(x) | | -15x+43=-10x+28 | | 47=2+9w | | 3(5y+5)=5y+45 | | 4a+8b=x | | 1/x=7/30 | | 16x+191=8x+127 | | -14x-153=-7x-90 | | -r/3=-100 | | -14+135=-7x+79 | | Y-z=x-y | | 17x+60=9x+36 | | 5/24=10/g | | 4/9a=1/9a-5/6 | | 5n-6=-106 | | 14x-76=8x-40 | | -6x-28=-3x-16 | | 0.09xX=72.44 | | -18x-83=-12x-47 | | -8x+32=-5x+17 | | h-6.5=15.2 | | 4y-3x=-84 | | -5x+26=-3x+16 | | 52=w/4 | | 9x+36=6x+18 | | F(x)=-1(x+1)(x-7) | | 3x+37=11.25 | | -18x+31=-12x+19 | | cos70=14/x | | 48-4x=7x | | 2-(x+1)=2x-11 | | 6(3x-2)=3-2(4x+1) |